Understanding the consumers’ multi-competing brand community engagement: A mix method approach - He, Kai; Liao, Junyun; Li, Fengyan; Sun, Hongguang (Frontiers in Psychology, 2023)
Introduction Participating in multiple competing brand communities simultaneously is common for consumers, which brings challenges for companies to manage brand communities and build strong brand-consumer relationships. Although previous studies have widely examined the drivers and outcomes of consumers’ engagement in an individual community, little is known about the multi-competing brand community engagement. Methods This paper explores the manifestation, categories, motivational drivers, and consequences of consumers’ MBCE through two studies using two different methodologies to fill this gap. Results By using netnography, study 1 shows that MBCE behaviors manifest in various ways, and can be classified into three categories: information-oriented MBCE, social-oriented MBCE, and oppositional MBCE. Study 2 indicates through a consumer survey that one reason that motivates consumers to participate in other competing brand communities is because of the attractiveness of other competing brands. Also, the results indicate that consumers’ product knowledge is positively associated with MBCE. Finally, the number of competing brand community engagements is positively related to brand switching intention. Discussion This article enriches the brand community literature and provides important implications on managing brand communities in a competing environment.